James Trevenen proposal and biographical sketch - Trevenen, James, 1760-1790.
Proposal (1787) made by Trevenen to the Russian government for the establishment of a trade route from the northwest coast of America through China in order to exchange furs for Chinese commodities. Includes an undated biographical sketch of Trevenen by an unknown writer.
British naval officer who later accepted a commission in the Russian navy.
Collection material in French, with English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Fur trade -- Northwest coast of North America; Trade routes -- North Pacific Ocean; China -- Commerce -- Russia -- History -- 18th century; Russia -- Colonies -- America; Russia -- Commerce -- History -- 18th century; Naval officers, British; Naval officers, Russian